PENGARUH JENJANG KARIR, MOTIVASI KERJA DAN KOMPENSASI KARYAWAN TERHADAP KINERJA KARYAWAN PADA BANK MANDIRI TASPENPASURUAN - Puspita, Dyah Aruning; Zulaikhah, Sitti; Sudiarto, Edi (Sekolah Tinggi Ilmu Ekonomi Nasional (STIENAS) Banjarmasin, 2024)
Abstract This research aims to analyze the influence of career level, work motivation, and compensation on employee performance at Bank Mandiri Taspen Pasuruan. Through a quantitative approach using multiple linear regression analysis, primary data obtained from employee questionnaires and secondary data from related literature. The research results show that career path, work motivation and compensation have a positive and significant influence on employee performance. This indicates that career development policies, high work motivation, and fair compensation are important factors that contribute to improving employee performance. Therefore, companies need to pay attention to and improve policies related to these three factors to ensure the achievement of organizational goals and overall employee satisfaction.